(untitled) (GEON Journal (Management, Organizations and Business), 2018)
The current implementation of the International Financial Reporting Standards "IFRS" in the Colombian area demand of public accountants, business managers and managers should be aware of the changes that brings to the accounting processes. In the present article a scientific and documentary literary review is made to shed light on the similarities and divergences between the Colombian accounting standard and the international ones in the subject of disclosures and notes to financial statements. One issue that has apparently been affected by this adoption is the notes to the financial statements. The methodology is based on a literary review carried out in indexed databases and in regulations (national and international). The issue is initially addressed from the national standard, then its application is identified from the guidelines of IFRS, to finally make comparisons of the case. It was found that the disclosures are directly related to the presentation and compliance with IFRS, similar to the case contained in Decree 2649 of 1993; In addition, both standards show that in the notes they must disclose the identifier data of the entity, although the national standard is not explicit in the presumption that by applying the regulations a reasonable presentation is obtained.